Evaluation of choroidal substructure perfusion in patients affected by systemic sclerosis: an optical coherence tomography angiography study. (3rd March 2020) - Ranjbar, M; Rothe, M; Klapa, S; Lange, T; Prasuhn, M; Grisanti, S; Riemekasten, G; Humrich, JY
Abstract : Objective : Vasculopathy in systemic sclerosis (SSc) is characterized by the obliteration of arterioles and a reduced capillary density in various tissues. In SSc, atrophic alterations of the choroid have been suggested based on morphological data acquired by optical coherence tomography (OCT). In this study, we aimed to assess the choroid in eyes of patients with SSc from a microcirculatory, dynamic point of view by adding optical coherence tomography angiography (OCTA) to the diagnostic spectrum. Method : SSc patients were enrolled, and age- and gender-matched healthy subjects were used as controls. In addition to basic ophthalmological and rheumatological examinations, individuals underwent enhanced-depth imaging OCT and OCTA. Subfoveal thicknesses of the choroid as well as all three choroidal vascular sublayers were measured and submacular perfusion values were evaluated. Results : In total, 12 patients with SSc and 12 matched controls were included. The median age of participants was 64 years. Submacular perfusion was significantly lower in the choriocapillaris (Δ = 0.72%; p = 0.045), Sattler's layer (Δ = 2.87%; p = 0.001), and Haller's layer (Δ = 2.69%; p = 0.018) of SSc patients compared to controls. Subfoveal thicknesses of Sattler's layer (Δ = 15 µm; p = 0.026) and Haller's layer (Δ = 41 µm; p = 0.045) were also significantly smaller in the SSc group. Conclusion : Choroidal microcirculation is impaired in SSc, even in patients without ophthalmological symptoms. Choroidal OCT and OCTA may offer additional biomarkers for SSc activity.